2014
DOI: 10.1016/j.bbmt.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Nonmyeloablative Peripheral Blood Haploidentical Stem Cell Transplantation for Refractory Severe Aplastic Anemia

Abstract: New transplant approaches are urgently needed for patients with refractory severe aplastic anemia (SAA) who lack a matched sibling or unrelated donor (UD) or who have failed UD or cord blood transplant. Patients with refractory SAA are at risk of later clonal evolution to myelodysplastic syndrome and acute leukemia. We report our pilot findings with haploidentical hematopoietic stem cell transplantation (haploHSCT) using uniform reduced-intensity conditioning with postgraft high-dose cyclophosphamide in 8 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 29 publications
1
99
0
Order By: Relevance
“…33 More recently, Clay et al 25 reported the UK experience on eight patients with SAA who underwent allogeneic PB transplantation from haploidentical donors and received posttransplant Cy with the same conditioning regimen described in our series. 25 In that series, four patients had already failed unrelated donor and/or cord blood transplants, and four had refractory acquired SAA. Another difference from our series is that all patients received PBSC grafts, which have been reported to be associated with decreased survival in patients with SAA.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…33 More recently, Clay et al 25 reported the UK experience on eight patients with SAA who underwent allogeneic PB transplantation from haploidentical donors and received posttransplant Cy with the same conditioning regimen described in our series. 25 In that series, four patients had already failed unrelated donor and/or cord blood transplants, and four had refractory acquired SAA. Another difference from our series is that all patients received PBSC grafts, which have been reported to be associated with decreased survival in patients with SAA.…”
Section: Discussionmentioning
confidence: 60%
“…34 Nevertheless, the results are similar to our series, with successful engraftment in most patients and low rates of GVHD. 25 In the UK cohort, two patients did not engraft because of anti-HLA Abs, and infection was the most common cause of death. In our series, despite the prior history of multiple transfusions, no patient had developed significant anti-HLA Abs, and this might be one of the reasons for our high rate (94%) of primary engraftment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] As far as we know, our case is the first that shows a patient with PNH and secondary aplastic anemia who achieved a prolonged disease-free state with haploidentical reduced intensity transplantation. In PNH patients who require an allogeneic transplant but do not have a fully matched related or unrelated donor, a haploidentical reduced intensity transplant may be an acceptable option.…”
mentioning
confidence: 74%
“…[2][3][4][5][6] Simultaneously, another group reported poor survival in eight heavily pre-treated patients with SAA, employing non-ablative conditioning and PTCY. 7 All patients in our study were heavily pre-transfused and were at high risk of graft failure as well as TRM. PTCY resulted in prompt and sustained engraftment in our cohort.…”
mentioning
confidence: 98%